A Framework for Mediating Medical and Social Models of Disability in Instrumental Teaching for Children with Down Syndrome. (July 2021) - Pickard, Beth
This article reflects upon the potential mediation of medical and social interpretations of disability through informing instrumental tuition with the strengths recognised in the learning profile of children with Down Syndrome. The learning profile is explored and critically discussed, and its reductionist, deficit-based potential identified; before considering the potential value of applying the evidence-based phenotype to musical provision. While a medical model of disability may interpret this learning profile as a list of deficiencies, this paper proposes that an informed, strength-based approach to teaching could empower students and challenge barriers to participation through suitably tailored provision, providing a relevant and constructive learning experience. This framework therefore aligns more closely with a Nordic relational model of disability that mediates the medical and social models, recognising disability as an interaction between impairment and the environment. Three case reports are presented to demonstrate and emphasise the range of personalities and individual differences between musicians with Down Syndrome, but also how this evidence-based approach can be applicable to many students, potentially contextualised within a "Universal Design for Learning" framework. A summary considers how raising awareness of constructive strategies for informed provision could develop confidence amongst practitioners, and thus in turn increase provision of relevant musical opportunities to students with additional learning needs, including Down Syndrome. In a critical conclusion, the notion of "differentiation" as perpetuating a dominant ableist discourse is considered and recommendations made with regard to furthering connections between critical social practices associated with Critical Disability Studies and music education.